2008
DOI: 10.1080/02713680802416670
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Retinal Neovascularization by shRNA Targeting HIF-1α

Abstract: RNAi targeting HIF-1alpha could inhibit the retinal neovascularization by approximately 65% through down-regulating the expression of HIF-1alpha and VEGF in the murine retinas, which may provide a powerful and novel therapeutic tool for ischemic-induced retinal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Exogenous genetic materials are degraded quickly in the target cells, and thus can only transiently inhibit the angiogenesis process, which leads to the regrowth of vessels after the administration of these antiangiogenesis agents to patients. 33 To achieve efficient long-term gene expression or pharmacodynamic action in the eye, intravitreal injection must be administered repeatedly to maintain the drug concentrations within a therapeutic range for a long period of time, which sometimes causes certain ocular complications, such as vitreous hemorrhage, retinal detachment or endophthalmitis. 32 Therefore, the application of drug-delivery systems to facilitate therapeutic efficacy and to minimize side effects may be of primary consideration in our study.…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous genetic materials are degraded quickly in the target cells, and thus can only transiently inhibit the angiogenesis process, which leads to the regrowth of vessels after the administration of these antiangiogenesis agents to patients. 33 To achieve efficient long-term gene expression or pharmacodynamic action in the eye, intravitreal injection must be administered repeatedly to maintain the drug concentrations within a therapeutic range for a long period of time, which sometimes causes certain ocular complications, such as vitreous hemorrhage, retinal detachment or endophthalmitis. 32 Therefore, the application of drug-delivery systems to facilitate therapeutic efficacy and to minimize side effects may be of primary consideration in our study.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA-MALAT1 also plays a key regulatory role in the pathological process of proliferative vitreoretinopathy (PVR) [20]. It is reported that RNAi targeting HIF-1α might inhibit the retinal neovascularization through decreasing the HIF-1αand VEGF expressions in the murine retinas [21]. Presently, the protective effect of LncRNA-MALAT1 on RGC damage in a high IOP rat model of glaucoma mediated by the PI3K/Akt signaling pathway has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…36 Therefore, many important targeting genes can be delivered, including vascular endothelial growth factor (VEGF) and hypoxia-inducible factor-1. [37][38][39][40][41][42] For example, Reich et al 37 reported that siRNAs directed against human VEGF effectively and specifically inhibit hypoxia-induced VEGF levels in human cell lines after adenoviral-induced human VEGF transgene expression in vivo. Our results also showed that high-concentration siRNA-PKCα delivered by electroporation has good knockdown efficacy at gene and protein levels (Figures 3 and 4).…”
Section: Discussionmentioning
confidence: 99%